Banking union and bank regulation: Banking sector stability in Europe - Franziska M. Bremus; Claudia Lambert (DIW Economic Bulletin, 2014)
Despite the most recent period of calm on the financial markets, the long-term resilience of the European financial system is not yet assured, even several years after the financial crisis began. However, the stability of the financial system playsa crucial role for real economic development and consequently for growth and prosperity. The financial crisis has shown that stricter regulation is required to improve the stability and resilience of the banking system. Further, it has become evident in recent years that banking supervision requires better international coordination in this age of globalization. The present report first analyzes current developments with regard to the European banking system: what regulatory and institutional changes have been introduced since the crisis? How have market structures and the stability of the banking system developed? Second, the report proposes recommendations to further promote the stability of the banking system: the European banking sector has not been fully consolidated and this should be driven forward as a matter of urgency. The transparency of the new regulatory and institutional structure should be increased. The close ties between banks and governments must also be loosened further. Beyond the adjustments planned to date, policy makers should promote alternative financing sources for small and medium-size firms, e.g. the direct access to capital markets.
Keywords: G21; G28; F42; 330; bank regulation; banking union; financial stability; bank market structures; institutional adjustments